Hadith Dissemination in the Digital Space: Unraveling the Contradictions of the “Sweeping-the-Road Clothing” Hadith Matn on Instagram within the Indonesian Context: Diseminasi Hadis di Ruang Digital: Mengurai Kontradiksi Matan Hadis Pakaian Menyapu Jalan di Instagram dalam Konteks Indonesia - Ach Faidi Rasyadi; Nopriani Hasibuan; Muhammad Habib Izzuddin Amin (Takwil: Journal of Quran and Hadith Studies, 2025)
In the digital era, Instagram has become an influential space for the dissemination of Hadith, yet it is often trapped in rigid textual interpretations. The phenomenon of “sweeping-the-road clothing” (garments that trail until they touch the ground) for Muslim women has become a polemic as the ideality of the Hadith text clashes with the reality of infrastructure, hygiene, and transportation safety in Indonesia. This research aims to unravel the contradictions between the Hadith text (matn) regarding the recommendation to lengthen clothing and the reality of its application in digital public spaces, as well as to identify audience reception patterns toward such content. This study employs a qualitative method with a library research approach. Primary data are sourced from posts by the Instagram accounts @cahaya_peradaban, @mahasiswa.salaf, and @fiqihwanita_. The analysis uses Stuart Hall’s Encoding-Decoding reception theory to map the reading positions of netizens. Research findings reveal a misalignment of understanding caused by the dominance of literalism in the presentation of Hadith and the neglect of Indonesia’s geographical context, which is humid and carries a risk of wet impurity (najis). Netizen responses are categorized into three positions: 1) Dominant-hegemonic, where the Hadith is accepted textually as a standard of piety; 2) Negotiated, where the principle of covering the awrah is accepted but practical adaptations are sought, such as wearing socks; and 3) Oppositional, which rejects the application of the Hadith as it is considered irrelevant and hazardous to safety in the Indonesian environment. This study emphasizes the importance of contextualization and comprehensive Hadith commentary (sharh) in digital da’wah to ensure religious messages remain relevant, hygienic, and aligned with the principles of public interest (maslahah).